2014
DOI: 10.1186/1749-8090-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose excision slows the progression of porcine coronary atherosclerosis

Abstract: BackgroundIn humans there is a positive association between epicardial adipose tissue (EAT) volume and coronary atherosclerosis (CAD) burden. We tested the hypothesis that EAT contributes locally to CAD in a pig model.MethodsOssabaw miniature swine (n = 9) were fed an atherogenic diet for 6 months to produce CAD. A 15 mm length by 3–5 mm width coronary EAT (cEAT) resection was performed over the middle segment of the left anterior descending artery (LAD) 15 mm distal to the left main bifurcation. Pigs recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…The direct involvement of EAT in CAD pathogenesis is also sustained by the evidence that intramyocardial segments of coronary arteries, which are, therefore, not in contact with EAT, are not affected by atherosclerosis [39] and that the selective surgical excision of the portion of EAT covering the coronary artery of a pig model of CAD attenuated the underlying plaque progression in vivo [40].…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 96%
“…The direct involvement of EAT in CAD pathogenesis is also sustained by the evidence that intramyocardial segments of coronary arteries, which are, therefore, not in contact with EAT, are not affected by atherosclerosis [39] and that the selective surgical excision of the portion of EAT covering the coronary artery of a pig model of CAD attenuated the underlying plaque progression in vivo [40].…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 96%
“…Embryologically and biochemically different from paracardial mediastinal fat (defined as adipose tissue external to the pericardium), EAT is associated with coronary artery disease (CAD), lipotoxic cardiomyopathy and atrial fibrillation. [1][2][3][4][5][6][7] As a metabolically active organ that releases cytokines and adipokines into the coronary arteries and myocardium [1][2][3][4][5] , EAT may directly alter myocardial contractile function independent of CAD. A recent in-vitro study demonstrated that EAT explanted from guinea pigs secrete factors that inhibit cardiomyocyte contractile function and induce insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, EFT was correlated with the angiographic severity of ACS, but was not correlated with the clinical outcome. It has been reported that the selective surgical excision of adipose tissue in direct contiguity with an epicardial coronary artery attenuated the progression of atherosclerosis in pigs (36). According to these results, it may be hypothesized that factors generated by the epicardial adipose tissue could contribute toward atherogenesis by direct diffusion through adventitia into the coronary intima-media and might locally contribute to stenosis progression.…”
Section: Discussionmentioning
confidence: 77%